PERFECTIONIST IDEAL OF EGALITARIAN SOCIETY - Абисова, М. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
The article is devoted to the social-philosophical analysis of political-cultural foundations and normative content of equality as a moral and political category in the liberal perfectionism concepts.